Presynaptic Inhibitory Effects of Fluvoxamine, a Selective Serotonin Reuptake Inhibitor, on Nociceptive Excitatory Synaptic Transmission in Spinal Superficial Dorsal Horn Neurons of Adult Mice - Orie Tomoyose; Daisuke Kodama; Hideki Ono; Mitsuo Tanabe (Elsevier, 2014)
Abstract.: Fluvoxamine, a selective serotonin (5-HT) reuptake inhibitor, has been shown to exert analgesic effects in humans and laboratory animals. However, its effects on spinal nociceptive synaptic transmission have not been fully characterized. Here, whole-cell recordings were made from dorsal horn neurons in spinal slices with attached dorsal roots from adult mice, and the effects of fluvoxamine on monosynaptic A-fiber- and C-fiber-mediated excitatory postsynaptic currents (EPSCs) evoked in response to electrical stimulation of a dorsal root were studied. Fluvoxamine (10 - 100 μM) concentration-dependently suppressed both monosynaptic A-fiber-and C-fiber-mediated EPSCs, which were attenuated by the selective 5-HT1A receptor antagonist WAY100635. In the presence of the selective 5-HT3 receptor antagonist tropisetron, fluvoxamine hardly suppressed A-fiber-mediated EPSCs, whereas its inhibitory effect on C-fiber-mediated EPSCs was not affected. Although fluvoxamine increased the paired-pulse ratio of A-fiber-mediated EPSCs, it increased the frequency of spontaneous and miniature EPSCs (sEPSCs and mEPSCs). Since sEPSCs and mEPSCs appeared to arise largely from spinal interneurons, we then recorded strontium-evoked asynchronous events occurring after A-fiber stimulation, whose frequency was reduced by fluvoxamine. These results suggest that fluvoxamine reduces excitatory synaptic transmission from primary afferent fibers via presynaptic mechanisms involving 5-HT1A and/or 5-HT3 receptors, which may contribute to its analgesic effects. Keywords:: fluvoxamine, patch clamp, excitatory postsynaptic current, strontium, spinal cord